2012
DOI: 10.1111/j.1365-2125.2011.04131.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction analysis between genetic polymorphisms and pharmacodynamic effect in patients treated with adjunctive cilostazol to dual antiplatelet therapy: results of the ACCEL‐TRIPLE (Accelerated Platelet Inhibition by Triple Antiplatelet Therapy According to Gene Polymorphism) study

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Compared with standard dual antiplatelet therapy, adjunctive cilostazol to dual antiplatelet therapy ('triple antiplatelet therapy') has a potential to reduce ischemic event occurrence after percutaneous coronary intervention.• The pharmacokinetic and pharmacodynamic effects of clopidogrel have been significantly influenced by the enzyme activity of the ABCB1 C3435T and the CYP2C19 system. • For the pharmacokinetics of cilostazol, genetic polymorphisms of the CYP3A5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
0
13
0
2
Order By: Relevance
“…The results demonstrated that CYP2C19*3 genetic polymorphism might function as an independent predictive factor of post‐PCI HPR and ischemic cardiovascular adverse events, while CYP2C19*2 and ABCB1 polymorphisms were found less correlated with the occurrence of HPR. Similarly, Kim et al and Zhang et al reported that ABCB1 polymorphism was not significantly associated with the increased risk of HPR, whereas CYP2C19 polymorphisms influenced antiplatelet response after clopidogrel treatment . In addition, patients with CYP2C19 LOF polymorphisms might have increased the risk of adverse cardiovascular events after PCI .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The results demonstrated that CYP2C19*3 genetic polymorphism might function as an independent predictive factor of post‐PCI HPR and ischemic cardiovascular adverse events, while CYP2C19*2 and ABCB1 polymorphisms were found less correlated with the occurrence of HPR. Similarly, Kim et al and Zhang et al reported that ABCB1 polymorphism was not significantly associated with the increased risk of HPR, whereas CYP2C19 polymorphisms influenced antiplatelet response after clopidogrel treatment . In addition, patients with CYP2C19 LOF polymorphisms might have increased the risk of adverse cardiovascular events after PCI .…”
Section: Discussionmentioning
confidence: 95%
“…In 24,25 In addition, patients with CYP2C19 LOF polymorphisms might have increased the risk of adverse cardiovascular events after PCI. 26 CYP2C19*2 mutation was considered to increase the risk of major adverse cardiovascular events in patients 27 and induce stent thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Следует отметить, что в ряде исследований были по-лучены противоположные данные [34]. Так, при изуче-нии зависимости частоты тромбозов стентов и АДФ-ин-дуцированной агрегации тромбоцитов от полимор-физма С3435Т гена MDR1 у 1525 пациентов, получав-ших клопидогрел, достоверных ассоциаций выявлено не было (р=0,89 и р=0,73, соответственно) [35].…”
Section: роль гликопротеина-р в кардиологииunclassified
“…14, 15 The latter observation has been consistently observed in various high-risk clinical settings (ACS, diabetes, and complex PCI), including the carriage of the CYP2C19 loss-of-function allele. 15, 16 In addition, Yang et al 17 reported that platelets expressed the adenosine A2b receptor, which was upregulated under stress in vivo. Adenosine A2b receptor stimulation was associated with decreased expression of the P2Y1 ADP receptor, implying that adenosine acts in platelets beyond its immediate influence on adenosine reuptake and platelet aggregation.…”
Section: Article P 2581mentioning
confidence: 99%
“…To date, several studies have demonstrated that adding cilostazol to DAPT significantly enhances platelet inhibition. 14- 16 Compared with double-dose clopidogrel therapy (150 mg/day), TAPT was associated with a greater decrease in adenosine diphosphate (ADP)-induced platelet aggregation. 14, 15 The latter observation has been consistently observed in various high-risk clinical settings (ACS, diabetes, and complex PCI), including the carriage of the CYP2C19 loss-of-function allele.…”
Section: Article P 2581mentioning
confidence: 99%